Muscle and Tendon Morphology in Early-Adolescent Athletes and Untrained Peers - Mersmann, Falk; Laube, Gunnar; Bohm, Sebastian; Arampatzis, Adamantios (Frontiers in Physiology, 2020)
Adolescent athletes can feature significantly greater muscle strength and tendon stiffness compared to untrained peers. However, to date it is widely unclear if radial muscle and tendon hypertrophy may contribute to loading-induced adaptation at this stage of maturation. The present study compares the morphology of the vastus lateralis (VL) and the patellar tendon between early-adolescent athletes and untrained peers. In fourteen male elite athletes (A) and 10 untrained controls (UC; 12-14 years of age) the VL was reconstructed from full muscle segmentations of magnetic resonance (MRI) sequences and ultrasound imaging was used to measure VL fascicle length and pennation angle. The physiological cross-sectional area (PCSA) of the VL was calculated by dividing muscle volume by fascicle length. The cross-sectional area (CSA) of the patellar tendon was measured over its length based on MRI segmentations as well. Considering body mass as covariate in the analysis, there were no significant differences between groups considering the VL anatomical cross-sectional area (ACSA) over its length or ACSAmax (UC: 24.0±8.3 cm2, A: 28.1 ± 5.3 cm2, p>0.05), yet athletes had significantly greater VL volume (UC: 440±147 cm3, A: 589±121 cm3), PCSA (UC: 31±9 cm2, A: 46±9 cm2), pennation angle (UC: 8.2±1.4°, A: 10.1±1.3°) and average patellar tendon CSA (UC: 1.01±0.18 cm2, A: 1.21±0.18 cm2) compared to the untrained peers (p < 0.05). However, the ratio of average tendon CSA to VL PCSA was significantly lower in athletes (UC: 3.4±0.1%, A: 2.7±0.5%; p < 0.05). When inferring effects of athletic training based on the observed ...